Minero-petrographical, chemical and physical characterisation of the ancient mortars from Fort Jesus Heritage Site, In Mombasa, Kenya - Asmait Hadish Sium; Gariy Zachary; Mutuku Raphael; John Mwero (Case Studies in Construction Materials, 2025)
Fort Jesus, one of the UNESCO World Heritage sites, faces degradation due to harsh environmental exposure, and inappropriate restoration, thus its existence in the future is at risk. The study's objective is to determine the composition of raw materials and mix proportion of the ancient mortars used in the construction of Fort Jesus. Eight samples were collected from different wall locations. A hydrochloric acid digestion test was used to separate the binder from the aggregate. X-ray powder diffraction (XRPD), Optical microscopy (OM), X-ray fluorescence (XRF), and scanning electron microscopy (SEM) were employed to analyse the mineralogical composition, petrographic characteristics, chemical properties, and microstructure of the mortars, respectively. High-carbonated calcite as a binder and quartz as a fine aggregate were dominant in all samples. The primary binder was found to be lime, mixed with different clay content. The binder-to-aggregate ratio was found to vary from 1:2.4–1:6.8 dominated by fine sand, likely sea sand. The findings of this study revealed variations in the mortars production methods among the Portuguese, Omani, and the Museum of Kenya applied in 1593,1698 and 2001 respectively. The main cause of the degradation was found to be the use of incompatible restoration mortar. Therefore, the findings from this study are vital for formulating compatible restoration mortar that aligns with the restoration needs of Fort Jesus.